The Role of Professional Teachers in Enhancing Students’ Learning Outcomes through the Gasing Kabataku Strategy - Gofur, Abdul (EDUPEDIA Publisher, 2025)
Purpose – This study aimed to explore the implementation of the GASING KABATAKU (Gampang, Asyik, Menyenangkan) method as an innovative approach to improve students' arithmetic skills and motivation in mathematics at MTs Negeri 14 East Jakarta. The study addresses the persistent issues of low numeracy and math anxiety among junior high school students in Indonesia. Methodology – An action research design was employed, involving 17 sessions split into two stages: teacher training and student implementation. Participants included mathematics and general subject teachers, along with seventh-grade students. The GASING KABATAKU intervention involved kinesthetic and visual learning activities, such as movement, songs, and manipulatives. Data were collected through pre- and post-tests, classroom observations, and teacher reflections. Quantitative data were analyzed descriptively, while qualitative data explored student engagement and motivation. Findings – The study found significant improvement in arithmetic achievement, with mean scores increasing from 60 to 85, and mastery levels rising from 55% to 90%. Qualitative observations indicated higher student motivation, reduced math anxiety, and increased classroom participation. The GASING KABATAKU method effectively enhanced both conceptual understanding and enthusiasm for learning. Novelty – This research integrates kinesthetic and rhythmic strategies into mathematics instruction, offering a replicable model for teacher professional development. Significance – The findings benefit mathematics educators, curriculum developers, and policymakers aiming to improve numeracy skills and foster student motivation in mathematics.